Evaluación técnico-financiera para 3 alternativas de procesamiento con el fin de aprovechar el gas producido en el campo La Creciente (2017)
The technologies of liquefied natural gas (LNG), gas-to-liquid technology (GTL) and electric thermogeneration were evaluated using the natural gas produced in La Creciente Block, which describes its geological generalities and existing production facilities. the gas produced and the supply and demand situation in the region of the Colombian Caribbean Coast are analyzed; In addition, a theoretical framework is presented and each process is simulated in the Aspen HYSYS simulator, which evaluates which alternative would be more feasible both technically and financially.